Pengaruh Penggunaan Aplikasi Identifikasi Jenis Bambu terhadap Sikap Peduli Pelestarian Bambu Siswa SDN Kota Bengkulu - Yeli Yulia Sari; Sri Ken Kustianti; Feri Noperman (Universitas Bengkulu, 2019)
This study aims to determine the Effect of Application Program Usage of Bamboo Type Identification as a Learning Media Against Attitude to Care of Bamboo Preservation of students class IV SD N Bengkulu City. This research is a quantitative research. The type of research used is quasi experimental research with the design of The Matching-Only Pretest-Posttest Control Group Design.. The population in this study is all students of grade IV SDN Bengkulu City. The sampling technique using Two Stage Random Sampling so as to obtain the class IVC SDN 82 Bengkulu city as the experimental class and class IVA SDN 76 Kota Bengkulu as the control class. The research instrument used in the form of student attitude test is questionnaire given by pretest and posttest given in experiment class and control class. Based on hypothesis test using t-test of two independent samples, obtained tcount (11,25)> ttable (1,677) at 5% significant level, hence can be concluded that there is influence of application program of bamboo type identification as learning media to attitude of bamboo conservation students of class IV SD N Bengkulu city.